Co-administration of dexmedetomidine and levobupivacaine results in better onset and duration of epidural anesthesia in lower extremity orthopedic surgery - Zulkifli, H.; Affandi, Ihsan; Zainal, Rizal; ., Theodorus (Bali Journal of Anesthesiology, 2019)
ABSTRACTBackground: The goal of this study is to know the efficacy of the addition of 0.5 mcg/kg dexmedetomidine to 15 mL isobaric 0.5% levobupivacaine on the onset and duration of sensory and motor blockade of epidural anesthesia in lower extremity orthopedic surgery.Methods: Randomized clinical double-blind trials were conducted in Dr. Mohammad Hoesin Hospital Palembang. A total of 34 patients underwent lower extremity surgery met the inclusion and exclusion criteria. Data were analyzed by independent t-test and Mann-Whitney test using SPSS 22.0 software.Result: The onset of sensory block in group D was 5.41±1.84 minutes compared to 17.59± 2.65 in Group C (p <0.001), as seen in Table 2. The sensory block duration was 362.41±25.66 minutes in Group D compared to 215.82±15.69 in Group C (p <0.001). The onset of the motoric block in group D was 16.53±1.81 minutes compared to 26.12±2.78 in Group C (p <0.001), while the motoric block duration was 301.29±20.55 minutes in Group D compared to 167.35±17.24 in Group C (p <0.001).Conclusion: The addition of 0.5mcg/kg dexmedetomidine to 15 ml isobaric 0.5% levobupivacaine in epidural anesthesia provide faster onset and prolonged duration in both motoric and sensory block in patients undergoing lower extremity surgery